2017
DOI: 10.14742/ajet.2789
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for the successful implementation of teacher educator design teams for ICT integration: A Delphi study

Abstract: Teacher educators often struggle to model effective integration of technology. Several studies suggest that the involvement of teacher educators in collaborative design is effective in developing the competences necessary for integrating information and communication technology (ICT) in teaching. In a teacher educator design team (TeDT), two or more teacher educators (re-)design curriculum materials together. For the successful implementation of TeDTs, conditions at both team and institutional levels have to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
1
41
0
9
Order By: Relevance
“…A short report was prepared with an anonymous summary of the participants' opinions from the previous round, and the experts were informed about the consensus range of factors and can compare this to their answers. This allows the participants to relate their responses to the participants' responses, to review a summary of the first round data and to make any necessary revisions (Becuwe et al, 2017). The procedure followed the process suggested by Hsu and Sandford (2007) in that the first round responses created the foundation for the questionnaire in the second round.…”
Section: Delphi Processmentioning
confidence: 99%
See 1 more Smart Citation
“…A short report was prepared with an anonymous summary of the participants' opinions from the previous round, and the experts were informed about the consensus range of factors and can compare this to their answers. This allows the participants to relate their responses to the participants' responses, to review a summary of the first round data and to make any necessary revisions (Becuwe et al, 2017). The procedure followed the process suggested by Hsu and Sandford (2007) in that the first round responses created the foundation for the questionnaire in the second round.…”
Section: Delphi Processmentioning
confidence: 99%
“…Shaikh and Khoja (2014) suggested that the consensus level is one of the fundamental elements in Delphi studies, and a sufficiently high consensus level should be utilised as a benchmark for retaining the factors that are preferred by participants in the first round. However, as there is no fixed measure to define the consensus level (Becuwe et al, 2017), variable statistics were used for consideration of the consensus level as suggested by various studies (Richardson, de Leeuw, & Dullaert, 2016;Gracht, 2012;Harmsen et al, 2015;Tharisara, Kanchana, & Turner, 2016;Williams, 2016;Hasson, Keeney, & McKenna, 2000;Hsu and Sandford,2007). Following (Bulger & Housner, 2007;Green, Jones, Hughes, & Williams, 1999;Lohuis, van Vuuren, & Bohlmeijer, 2014;Neuer Colburn, Grothaus, Hays, & Milliken, 2016), this study uses a consensus level of four for five-point Likert scale questions.…”
Section: Demographics Of Participantsmentioning
confidence: 99%
“…Second, Becuwe, Pareja Roblin, Tondeur, Thys, Castelein, and Voogt (2017) provide -through a Delphi study -an overview of the conditions that need to be taken into account for successfully implementing a TDT, at the level of the team and the institution. They stress that factors at the institutional level affect the team level; such that an innovative institutional culture will be reflected in the innovative character of the design task and approach of the TDT (Becuwe et al, 2017).…”
Section: Conditions For Successful Design Teamsmentioning
confidence: 99%
“…Second, Becuwe, Pareja Roblin, Tondeur, Thys, Castelein, and Voogt (2017) provide -through a Delphi study -an overview of the conditions that need to be taken into account for successfully implementing a TDT, at the level of the team and the institution. They stress that factors at the institutional level affect the team level; such that an innovative institutional culture will be reflected in the innovative character of the design task and approach of the TDT (Becuwe et al, 2017). At team level, the conditions for setting up successful TDTs can be grouped into four themes: the design task (long-term view; consisting of technological, pedagogical and content components); team composition (team members are open to innovation, trust each other, and are open to feedback); collaboration (members feel responsible for the design task and results); and role of the coach (flexible and adapts to needs of the members).…”
Section: Conditions For Successful Design Teamsmentioning
confidence: 99%
See 1 more Smart Citation